AGAMA DAN MANUSIA - Wardoyo Wardoyo (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
The paper is aimed to know the religion as the need inhuman life, religion as the basic of human need, and religion isfunctioning as the need for human. People need religion as guidance tolive in the world. Religion can be interpreted as a guide of life. Islam isreligion and it has a holly book called Al Qur‟an. It leads people howto live in the world properly. It also leads people how to do good seedsor to avoid bad seeds.